Damage tolerance analysis of aircraft reinforced panels - A. Pirondi; F. Carta (Fracture and Structural Integrity)
This work is aimed at reproducing numerically a campaign of experimental tests performed for the development of reinforced panels, typically found in aircraft fuselage. The bonded reinforcements can significantly reduce the rate of fatigue crack growth and increase the residual strength of the skin. The reinforcements are of two types: stringers and doublers. The former provides stiffening to the panel while the latter controls the crack growth between the stringers. The purpose of the study is to validate a numerical method of analysis that can predict the damage tolerance of these reinforced panels. Therefore, using a fracture mechanics approach, several models (different by the geometry and the types of reinforcement constraints) were simulated with the finite element solver ABAQUS. The bonding between skin and stiffener was taken either rigid or flexible due to the presence of adhesive. The possible rupture of the reinforcements was also considered. The stress intensity factor trend obtained numerically as a function of crack growth was used to determine the fatigue crack growth rate, obtaining a good approximation of the experimental crack propagation rate in the skin. Therefore, different solutions for improving the damage tolerance of aircraft reinforced panels can be virtually tested in this way before performing experiments.